(N~ELOWEK ROVDENNYJ DLQ PROESSII(B.s (NIZ INTERWX@ wQ^ESLAWA tIHONOWA(B.s - (NwQ^ESLAW tIHONOW(B.s; (N`(B.(Ni(B.(NkRILOW(B.s (NSOSTAWITELXs ((NmOSKWAs (Nasts, 2017)
(NwQ^ESLAW wASILXEWI^ tIHONOW(B-(NWYDA@]IJSQ AKTER(B,(NSIMWOL BLAGORODSTWA I MUVESTWA(B. (NNASTOQ]IJ RYCARX SOWETSKOGO I ROSSIJKOGO KINEMATOGRAFA ODIN IZ SAMYH UZNAWAEMYH I L@BIMYH AKTEROW(B.s
Keywords: (NMONOGRAFIQs